ANALISIS STABILITAS LERENG JALAN ALAHAN PANJANG DI BAWAH PENGARUH DRYING AND WETTING CYCLE - Anggriyeni, Vellya; Andayono, Totoh (Jurnal Applied Science in Civil Engineering, 2023)
Slopes can be formed naturally due to geological processes or human engineering as a link between the higher ground surface and the lower ground surface. Soil conditions must be stable so as not to cause landslides. Knowing the stability of a slope can be done by analyzing slope stability using the Circular Slope method and the GeoStudio 2012 Software Slope/W program. Data properties obtained from direct shear strength testing. After doing the research, it shows that using the Circular Slope method the Woptimum condition water content is 28.08%, the slope is in critical condition (slides have occurred) because it obtained a safety factor value of 1.179 (F between 1.07 - 1.25). In dry conditions, the water content is 25.272%, the safety factor value of the slope is in critical condition (slides have occurred) because it obtained a safety factor value of 1.082 (F between 1.07 - 1.25) and in conditions of 22.464% water content, the safety factor value of the slope in unstable conditions (ordinary/frequent landslides) because the safety factor values were 1.06 and 0.97 (F < 1.07 ). In the wetting condition, namely the water content of 30.888% and 33.696%, the safety factor value of the slope is in unstable conditions (ordinary landslides/occurs frequently) because the safety factor values are 0.883 and 0.751 (F < 1.07). Analysis of slope stability on the Alahan Panjang road using the GeoStudio 2012 Software Slope/W application uses three methods, namely Ordinary, Janbu and Bishop. The results of the three methods show that the effects of drying and wetting cause slopes to be in an unstable condition (slips usually occur), this is indicated by a safety factor value of <1.07.